1999
DOI: 10.1046/j.1432-1327.1999.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of C5‐cytosine methylation on the solution structure of d(GAAAACGTTTTC)2

Abstract: The solution structures of d(GAAAACGTTTTC) 2 and of its methylated derivative d(GAAAAMe 5 CGTTTTC) 2 have been determined by NMR and molecular modelling in order to examine the impact of cytosine methylation on the central CpG conformation. Detailed 1 H NMR and 31 P NMR investigation of the two oligomers includes quantitative NOESY, 2D homonuclear Hartmann±Hahn spectroscopy, double-quantum-filtered COSY and heteronuclear 1 H-31 P correlation. Back-calculations of NOESY spectra and simulations of double-quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…Furthermore, only small differences are discernable when structures with and without the C5 methyl group are compared in crystals (40,43) as well as in solution (41,42,44,45). The NOESY spectra of the d(CATA 2 T 2 ATG) 2 and d(CATA 2 U 2 ATG) 2 oligomers that have been investigated in the present study are in agreement with these earlier studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, only small differences are discernable when structures with and without the C5 methyl group are compared in crystals (40,43) as well as in solution (41,42,44,45). The NOESY spectra of the d(CATA 2 T 2 ATG) 2 and d(CATA 2 U 2 ATG) 2 oligomers that have been investigated in the present study are in agreement with these earlier studies.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of structural impact of C5 methylation as evidenced by Fig. 4 and previous studies (41,42,44,45) is therefore compatible with the large dynamical effects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…41 Finally, structural analysis by solution NMR and molecular modeling methods shows that replacement of cytosine by meC in a 12-mer oligonucleotide duplex with a single, central CpG dinucleotide step gives rise to a local narrowing of the minor groove, while the major groove becomes more shallow. 42 In summary, the reported physical and structural differences in CpG and meCpG sequence contexts do not provide any simple explanations for the unusual conformational switch of the 10R (−)-trans-anti- [BP]G adduct when the cytosine residue flanking the adduct is replaced by 5-methylcytosine in the 11-mer duplex studied in this work.…”
Section: Discussionmentioning
confidence: 65%
“…36,37 The impact of the methyl group at the 5-position of cytosine on the characteristics of double-stranded DNA have been studied by a variety of approaches. [38][39][40][41][42] Cyclization of ligated mixed-sequence oligonucleotides followed by analysis of electrophoretic mobilities showed that the changes in helical twist or intrinsic flexibility are not altered significantly by cytosine methylation. 40 However, in the case of an EcoRI decamer, methylation of the cytosine residue at the CpG dinucleotide steps lowers flexibility by ~30% and causes an underwinding by ~0.5 base-pair per turn.…”
Section: Discussionmentioning
confidence: 99%